An empirical Evaluation of the effect of service encounter on customer voluntary behavior: Exploration study of (TBI) customers - عبد الرسول حسين علي; كاظم فائق جواد (Journal of Economics and Administrative Sciences, 2013)
Purpose: To determine the impact of service encounter in stimulating voluntary customer behaviors. • Approach / methodology: It was selected a sample of customers Bank Iraqi Trade (TBI) was (105) individual, using a questionnaire designed in the light of previous studies, was drafted scale and tested in the light of a group of statistical methods developed (reliability coefficient, reliability coefficient composite, convergence). Then test hypotheses through structural equation modeling. • Results: The behaviors and characteristics of the service provider in effect urged bank customers to perform voluntary extra, as the service environment service encounter play a role in stimulating bank customer on voluntary behavior. • Originality/ value: The value of current research in theoretical frameworks service encounter, and to focus on voluntary customer behaviors, and himself search determine the impact of the service encounter on volunteer service